¿Tarsis era Tarteso? Lo que los textos bíblicos dicen (y no dicen) - Pereira Delgado, Álvaro 1979-; Díez Herrera, Pablo Antonio; Garzón-Moreno, Miguel Ángel (2023)
Most of archeologists and historians place the biblical Tarshish in Tartessos, although there are dissenting voices which set it in Tarsus of Cilicia, or in other locations. Scholars have presented different evidence of archaeological, philological, epigraphic, and literary nature. In the present research, we will focus on the specific biblical proof about the identification between Tarshish and Tartessos. We will study the most relevant biblical passages (Genesis 10:4; 1 Kings 10:22, 22;49; 2 Chronicles 9:21, 20:36; Isaiah 23; Ezekiel 26-28; etc.). These texts have frequently been used as clear historical evidence. Nevertheless, these are compositions that were written many years after the narrated events. In addition, it is necessary to consider the literary and rhetorical dimension of these works, whose interests were more religious and ideological than historical and geographical. We will try to clarify what can be said and what cannot (or should not) be said about Tarshish, based on the biblical texts in which this toponym appears.
La ubicación de la Tarsis bíblica en Tarteso goza hoy de bastante aceptación entre arqueólogos e historiadores, aunque hay voces disidentes que la ubican en Tarso de Cilicia o en otras localizaciones. Los estudiosos han esgrimido diferentes pruebas de índole arqueológica, filológica, epigráfica y literaria. En la presente investigación nos fijaremos en la específica prueba bíblica acerca de la identificación entre Tarsis y Tarteso. Estudiaremos los textos bíblicos más relevantes (Génesis 10,4; 1 Reyes 10,22; 22,49; 2 Crónicas 9,21; 20,36; Isaías 23; Ezequiel 26-28, etc.), que han sido empleados frecuentemente como evidencias históricas fehacientes. Se trata, no obstante, de composiciones que fueron escritas bastantes años después de los hechos narrados. Además, es necesario considerar el espesor literario y retórico de unas obras cuyos intereses eran más ideológicos y religiosos que históricos y geográficos. Trataremos así de perfilar qué se puede decir a partir de los textos bíblicos sobre el topónimo Tarsis y qué no se puede (o no se debería) decir.
Keywords: 1 Reyes; Ezequiel; Isaías; Jonás; Tarsis; Tarso; Tarteso